(untitled) (American International Journal of Education and Linguistics Research, 2019)
The purpose of this study is to identify the factors causing poor English language learning at high schools manly; Zahir Shahi and Temoor Shahi high schools. Furthermore, the quantitative approach applied in this study and the data have collected by Questionnaire, which had 11 items and made from the literature review and the data is analyzed with SPSS (Version 21) and clarified the mean and standard deviation. Based on the findings of this research, the main causes have been included namely; first, the lack of skillful teachers of English language at schools. Secondly, the lack of standard textbooks. Thirdly, lack of effective strategies for teaching this language.